Influence of metabolic syndrome information on macronutrient consumption decisions - Kyereboah, Eva Adomaa (Kansas State University, 2018)
Metabolic syndrome (MetS) continues to be a public health concern in the United States. The current prevalence rate is about 34% among American adults. One of the recommended line of treatment for the components of MetS is dietary behavior change. Although, many dietary recommendations guidelines are published to aid in better dietary choices, little is known about how effectively they alter dietary choices. Thus, the overall objective of this study was to examine the extent to which knowledge about the presence of metabolic syndrome components influenced macronutrient intake. Data from 2013-2014 National Health and Nutrition Examination Survey (NHANES) were used for the study. The variables used were taken from modules of the NHANES dataset: demographic, dietary (day 1 and 2 recall), questionnaire (blood Pressure & Cholesterol, medical condition, diabetes and weight history), examination (blood pressure and body measures) and laboratory (cholesterol – high density lipoprotein, and triglycerides and plasma fasting glucose). Daily macronutrients (calories, protein, carbohydrate, fat and total sugar) intake were regressed on knowledge of MetS components presence and demographic characteristics using Ordinary Least Square model. The results show that having information that one has diabetes was associated with a reduced intake of daily calories (160 kcal), carbohydrate (22.73 g) and total sugar (15.26 g). There was no significant association between protein and fat intakes and the knowledge of the presence of a metabolic syndrome component in the econometric model. Ageing was associated with increase in calorie (16 kcal/day), protein (0.502 g/day) and fat (0.66 g/day) intake. Males consumed higher amounts of all macronutrients than females. Higher education was associated with higher fat intake (5.09 g/day for High School and 4.54 g/day for college compared with those with less than high school education) but reduced sugar intake (8.86 g/day) for those with college education. It was found that 27.59% of individual’s who had diabetes did not know they had it, and about 41% of those who did know they were overweight had central obesity. The study concludes that compared to knowledge about high triglyceride levels, low high-density lipoprotein, diabetes, high blood pressure and overweight, knowledge about having diabetes seems to motivate people to change their dietary intake. This may be due to the immediate effect of diet on diabetic patients compared to the other MetS components. The result of this is that it may be appropriate to pursue drug therapy for addressing the other MetS components while diet change may be effective contributor to managing diabetes.
Keywords: Information; Metabolic syndrome components; Macronutrient intake